Antimalarial Activity of Human Group IIA Secreted Phospholipase A(2) in Relation to Enzymatic Hydrolysis of Oxidized Lipoproteins - Dacheux, Mélanie (Infect Immun, 2019)
The level of human group IIA secreted phospholipase A(2) (hGIIA sPLA(2)) is increased in the plasma of malaria patients, but its role is unknown. In parasite culture with normal plasma, hGIIA is inactive against Plasmodium falciparum, contrasting with hGIIF, hGV, and hGX sPLA(2)s, which readily hydrolyze plasma lipoproteins, release nonesterified fatty acids (NEFAs), and inhibit parasite growth. Here, we revisited the anti-Plasmodium activity of hGIIA under conditions closer to those of malaria physiopathology where lipoproteins are oxidized. In parasite culture containing oxidized lipoproteins, hGIIA sPLA(2) was inhibitory, with a 50% inhibitory concentration value of 150.0 ± 40.8 nM, in accordance with its capacity to release NEFAs from oxidized particles. With oxidized lipoproteins, hGIIF, hGV, and hGX sPLA(2)s were also more potent, by 4.6-, 2.1-, and 1.9-fold, respectively. Using specific immunoassays, we found that hGIIA sPLA(2) is increased in plasma from 41 patients with malaria over levels for healthy donors (median [interquartile range], 1.6 [0.7 to 3.4] nM versus 0.0 [0.0 to 0.1] nM, respectively; P < 0.0001). Other sPLA(2)s were not detected. Malaria plasma, but not normal plasma, contains oxidized lipoproteins and was inhibitory to P. falciparum when spiked with hGIIA sPLA(2). Injection of recombinant hGIIA into mice infected with P. chabaudi reduced the peak of parasitemia, and this was effective only when the level of plasma peroxidation was increased during infection. In conclusion, we propose that malaria-induced oxidation of lipoproteins converts these into a preferential substrate for hGIIA sPLA(2), promoting its parasite-killing effect. This mechanism may contribute to host defense against P. falciparum in malaria where high levels of hGIIA are observed.